The formation of multi-destination image: A study of China’s Greater Bay Area - Duan, Xialei; Lai, Ivan Ka Wai (Frontiers in Psychology, 2022)
Many governments promote the concept of multi-destination tourism to attract foreign visitors to stay longer in a region. This study constructs a higher-order multi-destination image model to examine how the unique cognitive images of Hong Kong, Macau, and Guangzhou collectively constitute the overall cognitive image of China’s Greater Bay Area (GBA). Then, it further examines how this overall cognitive image builds affective, overall, and conative images of the GBA. The results of an online survey of non-Chinese tourists from Guinea, Japan, New Zealand, the United Kingdom, and the United States show that cognitive images of three cities in the GBA take different weighting in constructing the overall cognitive image of the GBA. The overall cognitive destination image significantly influences the formation of the affective, overall, and conative images of the GBA region. For constructing the conative image, the affective image shows the greatest impact, overall cognitive image followed; the impact of the overall image is less. This study proposes theoretical implications for future regional tourism studies. Practical recommendations are also proposed.